1988
DOI: 10.1159/000180990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Recombinant Human Growth Hormone Preparation on the Urinary 15Nitrogen Balance in Growth-Hormone-Deficient Children

Abstract: In 10 patients with idiopathic growth hormone (GH) deficiency (9 boys and 1 girl, aged 7.5–14.5 years, mean 12.1 ± 2.2 years), urinary 15N-balance studies were performed before and on recombinant hGH (2 × 3 IU/m2 of body surface area subcutaneously on consecutive days). Before and on the 2nd day of recombinant hGH, 99% 15N-labeled ammonium chloride (0.05 g/kg, divided in 3 doses per day, corresponding to 389 ± 30 mg/m2 of 15N) was administered and 24 h uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Treatment with hGH has been shown to decrease uri nary nitrogen excretion in metabolic studies, using both classical metabolic and isotope (l5N) methods [4, [13][14][15][16][17]26], Previous work with rhGH has also demonstrated that the recombinant 22-kD hGH molecule exhibits the same biological behavior as pit-hGH when administered to GH-deficient children [27], The fall in urinary' nitrogen excretion in response to GH is mainly due to a decrease in the synthesis of urea [26,28] by shunting nitrogen from ureagenesis into growth-related processes via an increased hepatic synthesis and release of glutamate that is largely removed from the blood by sites located in the periphery [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with hGH has been shown to decrease uri nary nitrogen excretion in metabolic studies, using both classical metabolic and isotope (l5N) methods [4, [13][14][15][16][17]26], Previous work with rhGH has also demonstrated that the recombinant 22-kD hGH molecule exhibits the same biological behavior as pit-hGH when administered to GH-deficient children [27], The fall in urinary' nitrogen excretion in response to GH is mainly due to a decrease in the synthesis of urea [26,28] by shunting nitrogen from ureagenesis into growth-related processes via an increased hepatic synthesis and release of glutamate that is largely removed from the blood by sites located in the periphery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies suggested that the response to long-term GH therapy may be better in patients with more marked metabolic responses to short-term GH administration [17,27], However, others have failed to discover a relationship between increases in HV during GH treatment and changes in nitrogen excre tion in response to GH administration [26,29,30], Simi larly, in our study, there was no correlation between the changes in nitrogen metabolism during short-term GH administration and the subsequent increase in HV during long-term GH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The former approach is not new but the latter method has been little used (41)(42)(43)(44). Its potential advantages are several.…”
Section: Discussionmentioning
confidence: 99%
“…Small numbers of short children with growth hormone deficiency have been studied with I5N techniques in the past (41,42). More recently, Zachmann et al (43) used the I5N-retention test to show the biologic equivalency of recombinant and pituitary-derived hGH preparations.…”
mentioning
confidence: 99%
“…After hGH. the balance became considerably more posi tive in the GH-dcficicnt patients [45], while in subjects with normal GH secretion, such as girls with Turner syn drome. it remained almost unchanged [46], When normal subjects were given testosterone, there was a marked l5N retention, which was in the same order of magnitude as that induced by hGH in the GH-deficient patients.…”
Section: Synergistic Metabolic Effectsmentioning
confidence: 95%